2017
DOI: 10.1016/j.ajog.2017.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transcranial direct-current stimulation in women with provoked vestibulodynia

Abstract: Findings suggest that active transcranial direct-current stimulation is not more effective than sham transcranial direct-current stimulation for reducing pain in women with provoked vestibulodynia. Likewise, no significant effects were found on sexual function, vestibular sensitivity, or psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…1). The final analysis was made with 49 studies, 24 of tDCS 3,4,7,8,17,24,29,33,36,41,42,54,65,66,75,78,83,90,94,105,108,110,113,116 and 22 of rTMS. 1,6,15,22,23,35,44,5153,63,64,67,69,73,76,77,84,85,87,101,103 Countries involved in these studies are shown in supplementary file 2 (S2), available at http://links.lww.com/PR9/A35.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The final analysis was made with 49 studies, 24 of tDCS 3,4,7,8,17,24,29,33,36,41,42,54,65,66,75,78,83,90,94,105,108,110,113,116 and 22 of rTMS. 1,6,15,22,23,35,44,5153,63,64,67,69,73,76,77,84,85,87,101,103 Countries involved in these studies are shown in supplementary file 2 (S2), available at http://links.lww.com/PR9/A35.…”
Section: Resultsmentioning
confidence: 99%
“…Some tDCS studies did report adverse events in active groups. 78,83,94,104,113 Only 2 rTMS 1,50 and one tDCS studies failed to mention adverse events. In one tDCS study, it was not possible to state whether the adverse events were in the active or sham group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies covered a wide variety of pain types. Most trials enrolled male and female patients except (Fregni et al, 2006b ; Forogh et al, 2021 ) (fibromyalgia); (Divandari et al, 2019 ) (chronic pelvic pain); (Morin et al, 2017 ) (provoked vestibulodynia); and (Dutra et al, 2020 ; Pegado et al, 2020 ) (chronic abdominal pain), which recruited females only. One study did not present information on gender distribution (Samartin-Veiga et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sufficient information was accessible from 16 investigations ( n = 683) for short-term assessment. We did not extract data from (Morin et al, 2017 ; Young et al, 2020 ) as the necessary chronic pain scores were not available for the short-term analysis. Figure 2A revealed an overall effect of real stimulation (SMD: −0.43, 95% CI: −0.75 to −0.12, P = 0.007), but with considerable heterogeneity ( I 2 = 76.2%, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation